2002
DOI: 10.1002/j.2333-8504.2002.tb01878.x
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTIVE VALIDITY OF SAT® I: REASONING TEST FOR TEST‐TAKERS WITH LEARNING DISABILITIES AND EXTENDED TIME ACCOMMODATIONS

Abstract: The predictive validity of the SAT® I: Reasoning Test was examined for students who took the test with an extended time accommodation for a learning disability. The sample included college students with learning disabilities who took the SAT I between 1995 and 1998 with extended time accommodations. First year grade point average (FGPA) was used as a measure of student performance. Although positive, the adjusted correlation between FGPA and SAT scores was lower for test‐takers with a learning disability than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Also note that in both groups, students performed better on the Math section compared to the Critical Reading and Writing sections of the SAT. Furthermore, as previous researchers (Morgan & Huff, 2002;Cahalan et al, 2002) have found, the standard deviations are larger in the SWD-T group, indicating greater variability in the scores for students with learning disabilities than for the group of individuals without disabilities.…”
Section: Measuresupporting
confidence: 71%
“…Also note that in both groups, students performed better on the Math section compared to the Critical Reading and Writing sections of the SAT. Furthermore, as previous researchers (Morgan & Huff, 2002;Cahalan et al, 2002) have found, the standard deviations are larger in the SWD-T group, indicating greater variability in the scores for students with learning disabilities than for the group of individuals without disabilities.…”
Section: Measuresupporting
confidence: 71%
“…These studies indicate that there is an over-prediction of grade scores obtained during college years for students who utilized testing accommodations (Cahalan, Mandinach, & Camara, 2002;Camara, Copeland, & Rothschild, 1998;Zurcher & Bryant, 2001). This would suggest that, for some accommodations at least, accommodated scores do not have the same meaning as scores from standard administrations, to the extent that one cannot make the same predictions from each.…”
Section: Discussionmentioning
confidence: 99%
“…For students with disabilities, two research lines dominated, one related to testing and validation concerns that included but went beyond the postsecondary admissions focus of the 1980s and 1990s (Ekstrom and Smith 2002;Laitusis et al 2002), and the second on accessibility (Hansen et al 2004;Hansen and Mislevy 2006;Hansen et al 2005). For English learners, topics covered accessibility (Hansen and Mislevy 2006;Wolf and Leon 2009), accommodations (Young and King 2008), validity frameworks and assessment guidelines (Pitoniak et al 2009;Young 2009), and instrument and item functioning (Martiniello 2009;).…”
Section: Validity and Validationmentioning
confidence: 99%